PARTISIPASI KELOMPOK MASYARAKAT DALAM PENGELOLAAN KAWASAN HUTAN LINDUNG, KASUS DI HUTAN LINDUNG GUNUNG NONA KOTA AMBON PROPINSI MALUKU (PERENNIAL, 2010)
The management of a protection forest often faces a dilemma between the importance of conservation and the importance of the needs of the local people in the area. Managing the area will on’t be so effective and disturbed if there is only minimal participation and insufficient support in interaction from the local people. Various factors of heterogeneous people will influence the form of interaction that occurs between the people and the area. The aim of this study is to know and measure the participation of the local people in managing the protection forest and to analyse the characteristics (both individual and organizational) that influence the level of participation collectively in preserving the protected forest area. This research is designed as a survey research having the character of a descriptive co-relationship between the variable dependent i.e. Community participation and the variable of individual and organizational characters as a heterogeneous factor in protection forest area. This research population is the active community who manage the land (dusung) around the protection forest area in Gunung Nona (HLGN) in Ambon. Data analyses used tests the technical Chi square and its participation level test the co-efficient of the contingency. Results show that the characteristics (both individual and organizational) that have a close connection and influenced the level of participation in preserving the HLGN area are their knowledge about the protection forest, the scope of the authority of dusung land, the status of ownership of the dusung, the period of involvement in the organization and the relationship between the organizer and the public members in the organization. People’s participation in managing the HLGN is based on the perceived benefits and how they manage the dusung depends on their own character or morale.Key words: Participation, Heterogeneous, Dusung.